Streptomyces musisoli sp. nov., an actinomycete isolated from soil - Thitikorn Duangupama; Chakapong Intaraudom; Pattama Pittayakhajonwut; Chanwit Suriyachadkun; Sarin Tadtong; Pramote Sirirote; Somboon Tanasupawat; Chitti Thawai (INTERNATIONAL JOURNAL OF SYSTEMATIC AND EVOLUTIONARY MICROBIOLOGY, 2021)
).
Keywords: Genomics and Phylogenetic Studies; Plant Disease Resistance and Genetics; Microbial Natural Products and Biosynthesis